Modern Spanish women as agents of change : essays in honor of Maryellen Bieder - Smith, Jennifer, 1970 November 13-; Bieder, Maryellen (Bucknell University Press, 2019)
"This volume brings together cutting-edge research on modern Spanish women as writers, activists, and embodiments of cultural change, and honors Maryellen Bieder's invaluable scholarly contributions. The critical analyses are situated within their specific socio-historical context, and shed new light on nineteenth- and early twentieth-century Spanish literature, history, and culture"--